A chiral p(vdf-trfe-cfe) based quaternary ferroelectric polymer material and a method of making the same
Patent Information
- Application Number
- CN202511216909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-08-28
AI Technical Summary
[0006]本发明的目的在于提供一种手性P(VDF-TrFE-CFE)基四元嵌段铁电聚合物材料及其制备方法,旨在解决现有铁电聚合物存在的问题;本发明的手性铁电聚合物利用手性小分子与P(VDF-TrFE-CFE)发生化学反应形成新的嵌段(ME)而得到,且表现出与手性小分子对应的手性;该材料为首个兼具铁电性和手性的PVDF基聚合物;本发明的合成步骤短,制备过程简单,在室温下仅需一步即可制成
1、本发明将手性小分子与铁电聚合物P(VDF-TrFE-CFE)混合,常温条件下,在溶液中一步合成,通过简单的化学反应制备手性铁电聚合物,方法简单步骤快捷。2、手性小分子与P(VDF-TrFE-CFE) 相互作用,生成新的嵌段单元,并以此作为位点,诱导聚合物形成手性。3、本发明将手性和铁电性结合,首次通过在铁电聚合物嵌段中引入手性组分,得到手性PVDF基聚合物,该材料为首个兼具铁电性和手性的PVDF基聚合物。这不仅增加了铁电聚合物在极性点群中结晶的可能性,还拓宽了铁电聚合物在光学方面的潜在应用。4、本发明使用流延法或旋涂法即可得到手性铁电聚合物薄膜。
Smart Images

Figure CN120944006B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of novel functional polymer materials technology, and relates to a chiral quaternary ferroelectric block polymer material based on poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (PVDF-TrFE-CFE) and its preparation method, namely a chiral P(VDF-TrFE-CFE)-based quaternary block ferroelectric polymer material and its preparation method. Background Technology
[0002] Ferroelectric materials are a class of insulators with spontaneous polarization intensity that can be reoriented by an applied electric field. Ferroelectric materials exhibit the strongest piezoelectricity among known piezoelectric materials and are widely used in high-dielectric-constant capacitors, non-volatile memories, and optoelectronic devices.
[0003] Inorganic ferroelectric materials possess high ferroelectric properties, but they require high processing temperatures and exhibit poor flexibility. The ferroelectricity of polymers was first discovered in polyvinylidene fluoride (PVDF). Subsequently, its binary copolymers, such as poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) and terpolymers, such as poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (PVDF-TrFE-CFE), have gradually replaced inorganic materials in many electrical and optical applications due to their solution processability, low weight and cost, high flexibility and biocompatibility, and high polarization activity. These materials are used in commercial products such as wearable flexible sensors, medical imaging, underwater navigation, soft robots, and actuators.
[0004] Chirality is closely related to the rules of life and exists in many natural macromolecules, such as proteins, polysaccharides, and nucleic acids. The synthesis of chiral substances, especially chiral polymers, is one of the most popular problems in materials science and chemistry. The ferroelectricity of materials stems from the asymmetry of their crystal structure, and the asymmetry caused by chirality can increase the likelihood of ferroelectric materials crystallizing in polar point groups, thereby enhancing their ferroelectric properties. Furthermore, chiral materials themselves possess circular dichroism and circularly polarized luminescence properties. Combining chiral materials with ferroelectric materials can extend their applications to the optical field, such as optical sensors, enantiomer separation, ferroelectric liquid crystals, asymmetric catalysis, and 3D optical displays. These chirality-related chemical design strategies can promote the development of chiral synthesis, thus greatly enriching the content of ferroelectric chemistry. However, currently, among the three major ferroelectric material systems—inorganic ferroelectrics, molecular ferroelectrics, and polymer ferroelectrics—only molecular ferroelectrics possess chirality.
[0005] Since chirality exists only in organic compounds, how to prepare a chiral ferroelectric polymer and thus expand its applications in ferroelectric and optical fields is a major challenge. Summary of the Invention
[0006] The purpose of this invention is to provide a chiral P(VDF-TrFE-CFE)-based quaternary block ferroelectric polymer material and its preparation method, aiming to solve the problems existing in current ferroelectric polymers. The chiral ferroelectric polymer of this invention is obtained by chemically reacting chiral small molecules with P(VDF-TrFE-CFE) to form new blocks (MEs), and exhibits chirality corresponding to the chiral small molecules. This material is the first PVDF-based polymer that combines ferroelectricity and chirality. The synthesis steps of this invention are short and the preparation process is simple, requiring only one step at room temperature.
[0007] The technical solution of the present invention is a chiral P(VDF-TrFE-CFE)-based quaternary block ferroelectric polymer material, which is formed by the chemical reaction of chiral small molecules with P(VDF-TrFE-CFE) to form new blocks (MEs) and exhibits chirality corresponding to the chiral small molecules.
[0008] The molar content of ME blocks in the chiral ferroelectric polymer increases with increasing reaction time, but does not exceed 5%; the color of the chiral ferroelectric polymer deepens with increasing molar content of ME blocks, gradually changing from light yellow to dark yellow.
[0009] The chiral small molecules mentioned include, but are not limited to, chiral amine small molecules ( R / S )-2-amino-1-phenylethanol, ( R / S )-1-(4-bromophenyl)ethylamine, ( R / S )-N-benzyl-1-phenylethylamine, ( R / S )-α-methylbenzylamine, ( R / S )-phenoxy-2-propane or its hydrochloride, or chiral amino acid small molecules ( L / D )-Tryptophan, ( L / D )-Lysine, ( L / D )-Cyclohexylglycine, ( L / D )-Phenylglycine, ( L / D )-Serine or its hydrochloride.
[0010] Preferably, chiral small molecule selection ( R / S 1-(4-bromophenyl)ethylamine.
[0011] This invention provides a method for preparing a chiral P(VDF-TrFE-CFE)-based quaternary block ferroelectric polymer material as described above, the specific steps of which are as follows: Step 1: Add P(VDF-TrFE-CFE) powder to organic solvent A and stir at room temperature until fully dissolved to obtain a transparent solution B; Step 2: Add chiral small molecules to solution B and stir the reaction at room temperature under a nitrogen atmosphere to obtain solution C containing the product; Step 3: Slowly pour solution C into mixed solvent D, filter, and obtain yellow product E; Wherein, solvent D is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1 to 1:5; Step 4: Dissolve the yellow product E in organic solvent A to obtain a yellow solution. Pour the obtained yellow solution back into mixed solvent D, filter, and collect the solid. Step 5: Place the solid collected in Step 4 into a vacuum oven and dry it thoroughly to obtain a chiral ferroelectric polymer.
[0012] The organic solvent A is one of N,N-dimethylformamide (DMF), tetrahydrofuran, acetonitrile, acetone, dimethyl sulfoxide (DMSO), and 2-butanone.
[0013] The organic solvent A is selected as DMF.
[0014] In step one, the concentration of the transparent solution B is 20 mg / mL to 50 mg / mL.
[0015] The mass of the chiral small molecule added in step two is up to three times the mass of P(VDF-TrFE-CFE), and the reaction time is 1-10 days.
[0016] In step two, the mass of the chiral small molecule added is 1.5 times the mass of P(VDF-TrFE-CFE), and the reaction time is 5 days.
[0017] In step three, the volume of solvent D is 10-20 times that of solution C.
[0018] In step three, solvent D is a mixture of ethanol and deionized water with a volume ratio of 1:2.
[0019] In step four, the volume of organic solvent A is 1-2 times the volume of organic solvent A in step one.
[0020] In step four, the volume of mixed solvent D is 10-20 times the volume of organic solvent A in step four.
[0021] After repeating step four 2-5 times, the collected solids are ultrasonically cleaned 2-5 times with deionized water and ethanol, respectively.
[0022] The solid collected in step four is a filter cake.
[0023] The solids collected in step five are vacuum dried at a temperature not exceeding 60 °C for a time not less than 18 h.
[0024] The solid collected in step five is dried in a vacuum at a temperature of 40 °C for 24 h.
[0025] The present invention discloses the following technical effects: 1. This invention mixes chiral small molecules with ferroelectric polymer P(VDF-TrFE-CFE) and synthesizes them in a one-step solution at room temperature. The chiral ferroelectric polymer is prepared through a simple chemical reaction, making the method simple and rapid. 2. The chiral small molecules interact with P(VDF-TrFE-CFE) to generate new block units, which serve as sites to induce chirality in the polymer. 3. This invention combines chirality and ferroelectricity. For the first time, a chiral PVDF-based polymer is obtained by introducing a chiral component into the ferroelectric polymer block. This material is the first PVDF-based polymer possessing both ferroelectricity and chirality. This not only increases the possibility of ferroelectric polymers crystallizing in polar point groups but also broadens the potential applications of ferroelectric polymers in optics. 4. This invention allows for the preparation of chiral ferroelectric polymer films using either casting or spin coating methods. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a schematic diagram of the design of the present invention. M represents the corresponding chiral small molecule, and x, y, z, and k are the molar contents of VDF, TrFE, CFE, and ME blocks that connect the chiral small molecule M in the polymer, respectively. Among them, x, y, and z are 62%, 31.5%, and 6.5%, respectively, and the value of k is related to the reaction time and the molar ratio and type of chiral small molecules, and k is less than 5%. Figure 2 The chiral quaternary block ferroelectric polymer of Example 1 of this invention and pure P(VDF-TrFE-CFE) 1 H NMR comparison spectrum; Figure 3 The XRD phase purity comparison spectra of the chiral quaternary block ferroelectric polymer and pure P(VDF-TrFE-CFE) in Example 1 of the present invention are shown. Figure 4 The FTIR-ATR comparison spectra of the chiral quaternary block ferroelectric polymer of Example 1 of the present invention and pure P(VDF-TrFE-CFE) are shown. Figure 5 This is a comparison chart of the DSC curves of the chiral quaternary block ferroelectric polymer and pure P(VDF-TrFE-CFE) in Example 1 of the present invention. Figure 6The CD spectrum of the chiral quaternary block ferroelectric polymer of Example 1 of the present invention is shown below. Figure 7 This is a PE curve of the chiral quaternary block ferroelectric polymer of Example 1 of the present invention. Detailed Implementation
[0028] The chiral quaternary block ferroelectric polymer of this invention is obtained by chemically reacting chiral small molecules with P(VDF-TrFE-CFE), exhibiting chirality corresponding to the chiral small molecules. The synthesis of this invention is short and the preparation conditions are simple, requiring only one step at room temperature.
[0029] Example 1: Preparation of chiral quaternary block ferroelectric polymer P(VDF-TrFE-CFE-ME): Weigh 0.5 g of P(VDF-TrFE-CFE) powder into a round-bottom flask, add 15 mL of N,N-dimethylformamide (DMF), and stir at room temperature until completely dissolved; add 0.8 g ( R 1-(4-bromophenyl)ethylamine was reacted under a nitrogen atmosphere at room temperature with stirring for 5 days. The reaction solution was slowly poured into 200 mL of a 1:2 mixture of ethanol and deionized water. After filtration, an orange-yellow crude product was obtained. The crude product was dissolved again in 15 mL of DMF and then poured into 200 mL of a 1:2 mixture of ethanol and deionized water. This process was repeated twice. The obtained product was ultrasonically washed three times with deionized water to remove the solvent completely, and then ultrasonically washed three times with ethanol to remove water and any remaining amine. The orange-yellow product was placed in a vacuum oven and dried at 40 °C for 24 h to obtain an orange-yellow chiral ferroelectric polymer P(VDF-TrFE-CFE-RME).
[0030] Similarly, using ( S Chiral ferroelectric polymer P(VDF-TrFE-CFE-SME) was prepared using 1-(4-bromophenyl)ethylamine as a reactant.
[0031] Using nuclear magnetic resonance hydrogen spectroscopy (NMR) 1 The polymer was characterized by 1H NMR to determine the content of ME blocks. Deuterated acetonitrile was used as the solvent, and the results are as follows: Figure 2 As shown, the peaks with chemical shifts in the range of 7.6–7.2 ppm correspond to ( R / SThe hydrogen atom on the benzene ring in 1-(4-bromophenyl)ethylamine corresponds to the hydrogen atom on the ME block backbone, while the peak at 6.8-5.8 ppm corresponds to the hydrogen atom on the trifluoroethylene unit (TrFE). Since the content of TrFE (y) is known, the content of chiral small molecules (k) in P(VDF-TrFE-CFE-RME) can be calculated to be 1.16%, and the content of chiral small molecules (k) in P(VDF-TrFE-CFE-SME) can be calculated to be 1.36%.
[0032] The phase purity of the chiral ferroelectric polymer was characterized using X-ray diffraction (XRD) and compared with that of pure P(VDF-TrFE-CFE). The results are as follows: Figure 3 As shown. 2 θ The diffraction peak at 19.5° corresponds to the ferroelectric phase (β phase). The β phase content of the ferroelectric polymer hardly changed after the introduction of chiral small molecules, indicating that the introduction of chiral small molecules has almost no effect on the formation of the β phase.
[0033] The phase purity and characteristic functional groups of chiral ferroelectric polymers were characterized using attenuated total reflectance Fourier transform infrared spectroscopy (FTIR-ATR), and the results were compared with those of pure P(VDF-TrFE-CFE). Figure 4 As shown, compared to pure P(VDF-TrFE-CFE), the infrared spectra of P(VDF-TrFE-CFE-RME) and P(VDF-TrFE-CFE-SME) contain C=N double bonds, C=C double bonds, and benzene rings, proving the successful synthesis of the quaternary block polymer. Furthermore, their β-phase and α-phase contents are almost identical, further demonstrating that the introduction of chiral small molecules has virtually no impact on the formation of the β-phase.
[0034] The phase transition temperature and crystallinity of chiral polymers were characterized using differential scanning calorimetry (DSC), and the results are as follows: Figure 5 As shown, compared to pure P(VDF-TrFE-CFE), the melting peaks of P(VDF-TrFE-CFE-RME) and P(VDF-TrFE-CFE-SME) gradually shift towards lower temperatures, and the areas enclosed by the peaks are basically equal. This indicates that the introduction of the ME block lowers the melting point of the polymer, but the crystallinity remains almost unchanged. Furthermore, P(VDF-TrFE-CFE) exhibits a weak Curie transition at 35 °C, while the polymer with the chiral amine block exhibits a strong Curie transition around 50 °C. This suggests that the introduction of the new block weakens the barrier to the Curie transition.
[0035] The chirality of the polymer was characterized using a circular dichroism spectroscopy (CD) instrument. A DMF solution of the polymer was drop-coated onto a quartz glass substrate, and the test was performed after the solvent had completely evaporated. The results are as follows: Figure 6As shown, the CD spectra of P(VDF-TrFE-CFE-RME) and P(VDF-TrFE-CFE-SME) exhibit strong CD signal intensities, with absorption peaks at similar heights but opposite directions, showing a good mirror correspondence. This indicates that the chirality of the chiral small molecule was successfully introduced into the polymer, inducing the polymer to form the corresponding chirality.
[0036] The ferroelectric properties of polymers were characterized using a ferroelectric testing instrument. Figure 7 The figure shows the electric field-polarization (PE) curve of P(VDF-TrFE-CFE-SME) at a frequency of 1 kHz. As can be seen from the figure, the remanent polarization of the chiral polymer increases with increasing electric field, reaching 0.05 μC / cm at an electric field of 10 MV / m. 2 Under an electric field of 50 MV / m, the remanent polarization is 0.2 μC / cm. 2 This indicates that the chiral polymer has good ferroelectric properties.
[0037] Example 2: Preparation of chiral quaternary block ferroelectric polymer P(VDF-TrFE-CFE-ME): Weigh 0.5 g of P(VDF-TrFE-CFE) powder into a round-bottom flask, add 20 mL of tetrahydrofuran (THF), and stir at room temperature until completely dissolved; add 0.5 g ( S )-N-benzyl-1-phenylethylamine was reacted at room temperature under a nitrogen atmosphere for 7 days with stirring. The reaction solution was slowly poured into a 1:5 volume ratio of ethanol and deionized water, and filtered to obtain a light yellow crude product. The crude product was dissolved again in 25 mL of THF, and then poured into 300 mL of a 1:5 volume ratio of ethanol and deionized water, and this process was repeated twice. The obtained product was ultrasonically washed four times with deionized water and ethanol to thoroughly remove the solvent and any possible residual amine. The resulting orange-yellow product was placed in a vacuum oven and dried at 40 °C for 24 h to obtain a light yellow chiral ferroelectric polymer with a ME block content (k value) of 1.94%.
[0038] Example 3: Preparation of chiral quaternary block ferroelectric polymer P(VDF-TrFE-CFE-ME): Weigh 0.5 g of P(VDF-TrFE-CFE) powder into a round-bottom flask, add 10 mL of acetonitrile, and stir at room temperature until completely dissolved; add 0.6 g ( R2-Amino-1-phenylethanol was reacted under a nitrogen atmosphere at room temperature with stirring for 8 days. The reaction solution was slowly poured into 150 mL of a 1:3 volume ratio of ethanol and deionized water mixture, and filtered to obtain a yellow crude product. The crude product was dissolved again in 20 mL of acetonitrile, and then poured into 300 mL of a 1:3 volume ratio of ethanol and deionized water mixture, and this process was repeated three times. The obtained product was ultrasonically washed three times with deionized water and ethanol to thoroughly remove the solvent and any possible residual amine. The obtained yellow product was placed in a vacuum oven and dried at 45 °C for 18 h to obtain a yellow chiral ferroelectric polymer with a ME block content (k value) of 2.12%.
[0039] Example 4: Preparation of chiral quaternary block ferroelectric polymer P(VDF-TrFE-CFE-ME): Weigh 0.5 g of P(VDF-TrFE-CFE) powder into a round-bottom flask, add 25 mL of acetone, and stir at room temperature until completely dissolved; add 1.5 g ( L )-Lysine hydrochloride was reacted at room temperature under a nitrogen atmosphere for 3 days with stirring. The reaction solution was slowly poured into a 1:1 volume ratio of ethanol and deionized water, and filtered to obtain a light yellow crude product. The crude product was dissolved again in 30 mL of acetone, and then poured into 400 mL of a 1:1 volume ratio of ethanol and deionized water, and this process was repeated four times. The resulting product was ultrasonically washed twice with deionized water and ethanol to thoroughly remove the solvent and any possible residual amino acids. The resulting orange-yellow product was placed in a vacuum oven and dried at 60 °C for 36 h to obtain a light yellow chiral ferroelectric polymer with a ME block content (k value) of 0.97%.
[0040] Example 5: Preparation of chiral quaternary block ferroelectric polymer P(VDF-TrFE-CFE-ME): Weigh 0.5 g of P(VDF-TrFE-CFE) powder into a round-bottom flask, add 18 mL of DMSO, and stir at room temperature until completely dissolved; add 0.4 g ( L Tryptophan was reacted at room temperature under a nitrogen atmosphere with stirring for 1 day. The reaction solution was slowly poured into 250 mL of a 1:3.5 mixture of ethanol and deionized water, and filtered to obtain a light pink crude product. The crude product was dissolved again in 25 mL of DMSO, and then poured into another 250 mL of a 1:3.5 mixture of ethanol and deionized water, and this process was repeated five times. The resulting product was ultrasonically washed twice with deionized water and ethanol to thoroughly remove the solvent and any remaining amino acids. The resulting product was placed in a vacuum oven and dried at 50 °C for 24 h to obtain a light pink chiral ferroelectric polymer with a ME block content (k value) of 0.11%.
[0041] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material, characterized in that... It is formed by the chemical reaction of chiral small molecules with the CFE segment of P(VDF-TrFE-CFE) to generate ME blocks, exhibiting ferroelectricity and chirality corresponding to the chiral small molecules; the reaction process is as follows: Step 1, P(VDF-TrFE-CFE) powder is added to organic solvent A and stirred at room temperature until fully dissolved to obtain a transparent solution B; Step 2, chiral small molecules are added to solution B and stirred at room temperature under a nitrogen atmosphere to obtain a solution C containing the product; the chiral small molecules include chiral amine small molecules ( R )-2-amino-1-phenylethanol, ( S )-2-amino-1-phenylethanol, ( R )-1-(4-bromophenyl)ethylamine, ( S )-1-(4-bromophenyl)ethylamine, ( R )-N-benzyl-1-phenylethylamine, ( S )-N-benzyl-1-phenylethylamine, ( R )-α-methylbenzylamine, ( S )-α-methylbenzylamine, ( R )-phenoxy-2-propylamine or ( S )-Phenoxy-2-propylamine.
2. The chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 1, characterized in that... The molar content of ME blocks in the ferroelectric polymer increases with increasing reaction time, but does not exceed 5%; the color of the ferroelectric polymer deepens with increasing molar content of ME blocks, gradually changing from light yellow to dark yellow.
3. A method for preparing the chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 1, characterized in that... The specific steps are as follows: Step 1: Add P(VDF-TrFE-CFE) powder to organic solvent A and stir at room temperature until fully dissolved to obtain a transparent solution B; Step 2: Add chiral small molecules to solution B and stir the reaction at room temperature under a nitrogen atmosphere to obtain solution C containing the product; Step 3: Slowly pour solution C into mixed solvent D, filter, and obtain yellow product E; Wherein, solvent D is a mixed solvent of ethanol and deionized water in a volume ratio of 1:1 to 1:5; Step 4: Dissolve the yellow product E in organic solvent A to obtain a yellow solution. Pour the obtained yellow solution back into mixed solvent D, filter, and collect the solid. Step 5: Place the solid collected in Step 4 into a vacuum oven and dry it thoroughly to obtain a chiral ferroelectric polymer.
4. The method for preparing a chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 3, characterized in that... The organic solvent A is one of N,N-dimethylformamide (DMF), tetrahydrofuran, acetonitrile, acetone, dimethyl sulfoxide (DMSO), and 2-butanone.
5. The method for preparing a chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 3, characterized in that... In step one, the concentration of the transparent solution B is 20 mg / mL to 50 mg / mL.
6. The method for preparing a chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 3, characterized in that... The mass of the chiral small molecule added in step two is up to three times the mass of P(VDF-TrFE-CFE), and the reaction time is 1-10 days.
7. The method for preparing a chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 3, characterized in that... In step three, the volume of solvent D is 10-20 times that of solution C.
8. The method for preparing a chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 3, characterized in that... The volume of organic solvent A in step four is 1-2 times the volume of organic solvent A in step one; The volume of mixed solvent D in step four is 10-20 times the volume of organic solvent A in step four; After repeating step four 2-5 times, the collected solids are ultrasonically cleaned 2-5 times with deionized water and ethanol, respectively.
9. The method for preparing a chiral P(VDF-TrFE-CFE)-based quaternary ferroelectric polymer material according to claim 3, characterized in that... The solid collected in step five is vacuum dried at a temperature not exceeding 60 °C for a time of not less than 18 h.
Citation Information
Patent Citations
Preparation method of ferroelectric polymer film with high piezoelectric coefficient
CN118772457A
Circularly polarized light-responsive ferroelectric polymer and method of preparing thereof
KR1020230064850A